Divergence in digestive and metabolic strategies matches habitat differentiation in juvenile salmonids. Issue 9 (11th September 2022) - Monnet, Gauthier; Rosenfeld, Jordan S.; Richards, Jeffrey G.
Abstract: Divergent energy acquisition and processing strategies associated with using different microhabitats may allow phenotypes to specialize and coexist at small spatial scales. To understand how ecological specialization affects differentiation in energy acquisition and processing strategies, we examined relationships among digestive physiology, growth, and energetics by performing captive experiments on juveniles of wild coho salmon ( Oncorhynchus kisutch ) and steelhead trout ( O. mykiss ) that exploit adjacent habitats along natural low‐to‐high energy flux gradients (i.e., pools versus riffles) in coastal streams. We predicted that: (i) the specialization of steelhead trout to high‐velocity, high‐energy habitats would result in elevated food intake and growth at the cost of lower growth efficiency relative to coho salmon; (ii) the two species would differentiate along a rate‐maximizing (steelhead trout) versus efficiency‐maximizing (coho salmon) axis of digestive strategies matching their ecological lifestyle; and (iii) the higher postprandial metabolic demand (i.e., specific dynamic action, SDA) associated with elevated food intake would occupy a greater fraction of the steelhead trout aerobic budget. Relative to coho salmon, steelhead trout presented a pattern of faster growth and higher food intake but lower growth efficiency, supporting the existence of a major growth versus growth efficiency trade‐off between species. After accounting for differences in ration size between species, steelhead trout also presented higher SDA than coho salmon, but similar intestinal transit time and lower assimilation efficiency. Both species presented similar aerobic budgets since the elevated SDA of steelhead trout was largely compensated by their higher aerobic scope relative to coho salmon. Our results illustrate the key contribution of digestive physiology to the adaptive differentiation of juvenile growth, energetics, and overall performance of taxa with divergent habitat specializations along a natural productivity gradient. Abstract : The manuscript contrasts digestive physiology, bioenergetics, and aerobic budgets between juvenile steelhead trout and coho salmon with divergent habitat specializations along a natural productivity gradient in coastal streams (coho occupy low energy flux pools, steelhead occupy high energy flux riffles). Faster‐growing steelhead trout emerged as typical energy (rate)‐maximizers through the elevation of both food intake and postprandial metabolism (specific dynamic action, SDA) at the cost of lower food processing efficiency (e.g., shorter transit duration at a given ration); by contrast, slower‐growing coho salmon emerged as typical efficiency‐maximizers with lower food consumption and postprandial metabolism but higher assimilation and growth efficiency. Our results illustrate the key contribution of digestive physiology to the adaptive differentiation of juvenile growth, energetics, and overall performance of taxa with divergent habitat specializations along a natural productivity gradient.